Glycemic index values of multifloral Turkish honeys and effect of their consumption on glucose metabolism - Soylu, Meltem; Atayoğlu, Timuçin; İnanç, Neriman; Silici, Sibel (Taylor and Francis, 2015)
The purpose of this study was to investigate the glycemic index (GI) of five honeys from different geographical origin in Turkey and the effect of their consumption on glucose metabolism. Five multifloral honeys (Bingol, Semdinli, Kayseri, Yuksekova, and Mu) were used in this study. Processing data from twenty healthy volunteers, GI values were determined from the glycemic values using the incremental area method. The serum insulin and C-peptide levels were also measured just before and 120min after the test. Semdinli and Yuksekova honeys were determined to have low GI while Kayseri and Bingol honeys have medium GI, and Mu honey has the highest GI. No significant correlation has been found between the GI values and sugar contents of the honeys (r=0.42) (p>0.05). Two hours after ingestions, all the honey samples with the exception of Bingol honey have given rise to a statistically significant decrease in serum glucose levels (p<0.05). Honeys have also given rise to a decrease in insulin levels, and this decrease is statistically significant after Semdinli honey. Meanwhile, C-peptide levels generally gave rise to an increase after honey ingestion, and this increase is not statistically significant, except for Mu honey (p>0.05). A comparative research is needed on healthy and diabetic individuals as a future recommendation.

El propo´sito de este estudio es investigar el ı´ndice gluce´mico (IG) de cinco mieles de distinta procedencia geogra´fica de Turquı´a, y el efecto de su consumo sobre el metabolismo de la glucosa. Se utilizaron cinco mieles multiflorales (Bingo¨l, S¸emdinli, Kayseri, Yuksekova y MUS) en el presente estudio. Tras el procesado de los datos de veinte voluntarios sanos, se determinaron los valores de GI a partir de los valores de glucemia mediante el me´todo del a´rea incrementado. Los niveles se´ricos de insulina y pe´ptido C tambie´n se midieron antes y a los 120 minutos despue´s de la prueba. Las mieles de S¸emdinli y Yuksekova mostraron bajo valores bajos GI, mientras que las mieles de Kayseri y Bingo¨l tienen GI medio y la miel de Mus¸ tiene el GI ma´s alto. No se ha encontrado correlacio´n significativa entre los valores de GI y el contenido de azu´car de las mieles (r = 0,42) (p> 0,05). Dos horas despue´s de la ingestio´n, todas las muestras de miel con la excepcio´n de la miel de Bingo¨l, han dado lugar a una disminucio´n estadı´sticamente significativa de los niveles de glucosa en suero (p 0,05). Se necesita una investigacio´n comparativa de individuos sanos y diabe´ticos para futuras recomendaciones
Ndice glucé mico de mieles turcas multiflorales y efecto de su consumo en el metabolismo de la glucose
WOS: 000374902200002
Keywords: Honey; Glycemic Index; Glucose Metabolism; Nutrition